2016
DOI: 10.1107/s2056989016013359
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of methyl 4-(4-hydroxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate monohydrate

Abstract: The title hydrate crystallizes with two formula units in the asymmetric unit (Z′ = 2). The organic mol­ecules form a dimer, linked by a pair of N—H⋯O hydrogen bonds. Further hydrogen bonding together with weak C—H⋯π and π–π inter­actions further consolidates the packing, generating a three-dimensional network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One structure (CUZVAW) [43] forms hydrogen bonding through N−H⋅⋅⋅O and O−H⋅⋅⋅O interactions and another structure (RAPJOI) [44] forms hydrogen bonding through N−H⋅⋅⋅O interaction only. From the CSD analysis, the five hydrated forms of DHPM were observed, i. e. (ESOVAL), [45] (POWXIJ), [46] (NOTKEO), [47] (XISMES), [48] and (GALBOL), [49] which form hydrogen bonding with a water molecule in the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One structure (CUZVAW) [43] forms hydrogen bonding through N−H⋅⋅⋅O and O−H⋅⋅⋅O interactions and another structure (RAPJOI) [44] forms hydrogen bonding through N−H⋅⋅⋅O interaction only. From the CSD analysis, the five hydrated forms of DHPM were observed, i. e. (ESOVAL), [45] (POWXIJ), [46] (NOTKEO), [47] (XISMES), [48] and (GALBOL), [49] which form hydrogen bonding with a water molecule in the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…One structure (CUZVAW) [43] forms hydrogen bonding through NÀ H•••O and OÀ H•••O interactions and another structure (RAPJOI) [44] forms hydrogen bonding through NÀ H•••O interaction only. From the CSD analysis, the five hydrated forms of DHPM were observed, i. e. (ESOVAL), [45] (POWXIJ), [46] (NOTKEO), [47] (XISMES), [48] and (GALBOL), [49] which form hydrogen bonding with a water molecule in the crystal structure. Furthermore, it is observed that (OZOHAO) [50] crystallizes with methanol solvent, (IVASII) [51] crystallizes with ethanol, and (GALJUB) [52] crystallized with acetic acid in their crystal structures.…”
Section: Cambridge Structural Database (Csd) Surveymentioning
confidence: 99%
“…The dihedral angles between the planes of the six‐membered tetrahydropyrimidine ring with its 4‐hydroxyphenyl and ester substituents are 86.78(0.10)° and 7.9(0.13)°, respectively. It is interesting to note that this monohydrated form exists as a new polymorph with two molecules in the asymmetric unit with Z ′ = 2 in the triclinic system with similar intermolecular hydrogen bonds, the detailed crystal structural analysis of Z ′ = 2 form is already reported …”
Section: Resultsmentioning
confidence: 94%